2020
DOI: 10.1177/2325967120960088
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Allograft Transplant of the Patella Using Femoral Condylar Allografts: Magnetic Resonance Imaging and Clinical Outcomes at Minimum 2-Year Follow-up

Abstract: Background: Fresh osteochondral allograft transplant (OCA) has good outcomes in the knee. However, donor tissue for patellar OCA is limited. Outcomes after nonorthotopic OCA of the patella using more readily available femoral condylar allograft (FCA) tissue have not been previously reported. Purpose: To assess short-term magnetic resonance imaging (MRI) and minimum 2-year clinical outcomes of nonorthotopic patellar OCA using an FCA donor. Study Design: Case series; Level of evidence, 4. Methods: A prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…20,21 Although the literature comparing imaging assessments between orthotropic and nonorthotopic OCA is exceedingly limited, the existing studies have displayed comparable scores between the two. 20,22-25 This aligns with the findings in our study demonstrating no difference in the imaging analysis of fresh precut OCA cores compared to size matched condylar grafts.…”
Section: Discussionsupporting
confidence: 90%
“…20,21 Although the literature comparing imaging assessments between orthotropic and nonorthotopic OCA is exceedingly limited, the existing studies have displayed comparable scores between the two. 20,22-25 This aligns with the findings in our study demonstrating no difference in the imaging analysis of fresh precut OCA cores compared to size matched condylar grafts.…”
Section: Discussionsupporting
confidence: 90%
“…Maintenance of native surface topography is equally important in the patella, and the differences in radius of curvature between the patella and femoral condyle are much greater than any differences between femoral condyles. In the study by Lin et al, 10 the authors reported that the graft was always harvested at the same location, the trochlear-condylar junction, and although no explanation was provided as to why this graft harvest location was selected, we surmise that this location was chosen in an effort to match patellar topography. The authors likely had a variety of locations on the patella which required grafting, and we question whether the radius of curvature differences can be reliably matched using this harvest site.…”
mentioning
confidence: 93%
“…We congratulate Lin et al 10 on their recent study entitled “Osteochondral Allograft Transplant of the Patella Using Femoral Condylar Allografts: Magnetic Resonance Imaging and Clinical Outcomes at Minimum 2-Year Follow-up.” In this case series, minimum 2-year follow-up PROs and minimum 6-month postoperative magnetic resonance imaging (MRI) findings were assessed in 25 and 20 patients, respectively, who underwent OCA to the patella or patella and trochlea using a femoral condyle allograft (FCA). The rationale for this approach is based on the scarcity of patellar grafts compared to that of the femoral condyle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 However, osteochondral grafting to the patella is still performed with an open approach, with arthrotomy and patellar eversion, to provide the necessary perpendicular access. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%